THE ROLE OF THE ANALYSIS OF THE FINANCIAL CONDITION IN THE DEVELOPMENT OF THE FINANCIAL POLICY OF THE ENTERPRISE (Conferencea, 2022)
In this article, the role of the analysis of the financial condition in the development of the financial policy of the enterprise was considered. And also the economic situation of the enterprise, the transition to financial management based on the financial and economic condition, taking into account the setting of strategic goals for the enterprise, strategic tasks in the analysis of the development of the financial policy of the enterprise, the development of predictive models of the financial condition of the enterprise were considered.